Aspek Hukum Penanganan Pasien Tuberkulosis Berbasis Perlindungan Hak Asasi Manusia - Puji Krisdiyantoro; Sulis Rahayu (Jurnal Syntax Admiration, 2024)
Handling of tuberculosis patients in a legal context based on the protection of human rights has been carried out through juridical instruments in various laws and regulations. However, the complexity of the challenge of providing effective care while respecting patient rights is often overlooked. This research uses a normative juridical research type, with a statutory and conceptual approach. Library collection of legal materials. Analysis uses qualitative descriptive. Research results: (1) Protection of human rights in treating tuberculosis patients is carried out by considering ethics and legality governing access to health services, patient privacy, and participation in decision making. (2) Policies that are more inclusive and sensitive to patients' human rights, including community empowerment and increasing awareness about tuberculosis, are needed to increase the effectiveness of tuberculosis treatment while respecting individual dignity and rights. The implication is that there is an integration of human rights principles in the regulations for treating tuberculosis to achieve sustainable and fair health goals for all.